Photosynthetic Versatility in the Genome of Geitlerinema sp. PCC 9228 (Formerly Oscillatoria limnetica ‘Solar Lake’), a Model Anoxygenic Photosynthetic Cyanobacterium - Grim, Sharon L.; Dick, Gregory J. (Frontiers in Microbiology, 2016)
Anoxygenic cyanobacteria that use sulfide as the electron donor for photosynthesis are a potentially influential but poorly constrained force on Earth’s biogeochemistry. Their versatile metabolism may have boosted primary production and nitrogen cycling in euxinic coastal margins in the Proterozoic. In addition, they represent a biological mechanism for limiting the accumulation of atmospheric oxygen, especially before the Great Oxidation Event and in the low-oxygen conditions of the Proterozoic. In this study, we describe the draft genome sequence of Geitlerinema sp. PCC 9228, formerly Oscillatoria limnetica ‘Solar Lake’, a mat-forming diazotrophic cyanobacterium that can switch between oxygenic photosynthesis and sulfide-based anoxygenic photosynthesis. Geitlerinema possesses three variants of psbA, which encodes protein D1, a core component of the photosystem II reaction center. Phylogenetic analyses indicate that one variant is closely affiliated with cyanobacterial psbA genes that code for a D1 protein used for oxygen-sensitive processes. Another version is phylogenetically similar to cyanobacterial psbA genes that encode D1 proteins used under microaerobic conditions, and the third variant may be cued to high light and/or elevated oxygen concentrations. Geitlerinema has the canonical gene for sulfide quinone reductase (SQR) used in cyanobacterial anoxygenic photosynthesis and a putative transcriptional regulatory gene in the same operon. Another operon with a second, distinct sqr and regulatory gene is present, and is phylogenetically related to sqr genes used for high sulfide concentrations. The genome has a comprehensive nif gene suite for nitrogen fixation, supporting previous observations of nitrogenase activity. Geitlerinema possesses a bidirectional hydrogenase rather than the uptake hydrogenase typically used by cyanobacteria in diazotrophy. Overall, the genome sequence of Geitlerinema sp. PCC 9228 highlights potential cyanobacterial strategies to cope with fluctuating redox gradients and nitrogen availability that occur in benthic mats over a diel cycle. Such dynamic geochemical conditions likely also challenged Proterozoic cyanobacteria, modulating oxygen production. The genetic repertoire that underpins flexible oxygenic/anoxygenic photosynthesis in cyanobacteria provides a foundation to explore the regulation, evolutionary context, and biogeochemical implications of these co-occurring metabolisms in Earth history.